2023
DOI: 10.2147/cmar.s411901
|View full text |Cite
|
Sign up to set email alerts
|

The Circular RNA circFGFR4 Facilitates Resistance to Anti-PD-1 of Triple-Negative Breast Cancer by Targeting the miR-185-5p/CXCR4 Axis

et al.

Abstract: Purpose One of the most catastrophic malignant tumors is triple negative breast cancer (TNBC). It is characterized by rapid progression in the clinic. CircRNAs are abnormally expressed in almost all cancers and play important roles in tumor immune evasion. Nevertheless, the biological roles of the circular fibroblast growth factor receptor 4 RNA (circFGFR4) in TNBC remain unclear. Methods The expression of circFGFR4 in TNBC tissues and paired nontumor tissues was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…CircFGFR4 is overexpressed in TNBC. CircFGFR4 acts as a decoy of miR-185-5p and increases the expression of CXCR4, so overexpression of circFGFR4 led to reduced infiltration of CD8+ T cells and enhanced resistance against anti-PD-1 immunotherapy in TNBC [ 68 ]. The circHIPK3 level is elevated and associated with a lower immunotherapy response in breast cancer [ 79 ].…”
Section: Main Textmentioning
confidence: 99%
“…CircFGFR4 is overexpressed in TNBC. CircFGFR4 acts as a decoy of miR-185-5p and increases the expression of CXCR4, so overexpression of circFGFR4 led to reduced infiltration of CD8+ T cells and enhanced resistance against anti-PD-1 immunotherapy in TNBC [ 68 ]. The circHIPK3 level is elevated and associated with a lower immunotherapy response in breast cancer [ 79 ].…”
Section: Main Textmentioning
confidence: 99%
“…The circular RNA circFGFR4 plays a crucial role in immune evasion and resistance to anti-PD-1 immunotherapy in TNBC by modulating the miR-185-5p/CXCR4 axis. Elevated levels of circFGFR4 were associated with reduced infiltration of CD8 + T cells in tumor tissues and resistance to anti-PD-1 immunotherapy in both TNBC patients and mice with TNBC tumors [ 99 ]. As well as, the binding of miR-149-3p to the 3'UTRs of mRNAs that encode T-cell inhibitor receptors such as PD-1, TIM-3, BTLA, and Foxp1 was predicted in breast cancer.…”
Section: Micrornas: Bridging the Gap Between Gene Regulation Immune C...mentioning
confidence: 99%
“…In addition, CircDUSP1 enhances expression of the disheveled binding antagonist of beta-catenin 2 (DACT2) via miR-761, thereby promoting TNBC sensitivity to paclitaxel [ 40 ] ; circUBE2D2 silences miR-512-3p to enhance CDCA3 to promote doxorubicin resistance in TNBC [ 41 ] ; and CircNCOR1 mediates TNBC radiotherapy resistance via hsa-miR-638 [ 42 ] . At the immune microenvironment level, circFGFR4 promotes TNBC immune evasion and resistance to PD-1 immunotherapy through miR-185-5p [ 43 ] . A number of circRNA-miRNA networks were summarized in Table 1 .…”
Section: The Function Of Circular Rna In Tnbcmentioning
confidence: 99%
“…Using a patient-derived organoid, they revealed that circCREIT overexpression greatly enhanced doxorubicin sensitivity of TNBC cells and demonstrated that this function is mainly achieved by stabilizing PKR [ 97 ] . In addition, circNCOR1 was shown to modulate TNBC radiotherapy resistance [ 42 ] , and circFGFR4 was associated with TNBC immunotherapy resistance [ 43 ] . Although basic research has demonstrated that circRNAs play an important role in TNBC resistance, relevant clinical trials have not yet been performed.…”
Section: The Role Of Circular Rna In Tnbc Progressionmentioning
confidence: 99%
See 1 more Smart Citation